Road traffic accident: An emerging public health problem in Assam - Pranab Jyoti Bhuyan; Faruquddin Ahmed (Wolters Kluwer Medknow Publications, 2013)
Background: In the northern states, there is hardly any scientific study except road traffic accidents (RTAs) statistics obtained by the Ministry of Home whereas the main way of transportation is by road. There is the increasing load of motor vehicles on the already dilapidated roadways which has resulted in the increasing trend of RTAs in Assam. Objectives: To find out the prevalence, probable epidemiological factors and morbidity and mortality pattern due to RTAs in Dibrugarh district. Materials and Methods: Descriptive study was carried out in Dibrugarh district from September 1998 to August 1999 under the department of Community Medicine. The information was collected from Assam Medical College and Hospital and cross checked with the police report. A medical investigation including interview, clinical and radiological investigation was carried out; in case of fatality, post-mortem examination was examined in details. An on the spot investigation was carried out in accessible RTAs to collect the probable epidemiological factors. Results: RTAs affected mainly the people of productive age group which were predominantly male. Majority of the RTAs were single vehicle accidents and half of the victims were passengers. Accident rate was maximum in twilight and winter season demanding high morbidity and mortality. Head and neck, U.limb and L.limb were commonly involved. Conclusion: RTAs is a major public health problem in Assam which needs more scientific study.